Pengaruh umur induk dan posisi peletakan telur pada mesin tetas terhadap daya tetas telur ayam buras (Gallus gallus domesticus). - - Rama; Satrio Wibowo; Lisnawaty Silitonga (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
The aim of this research to knew the influence of different hens age and laying position of eggs in incubator, interaction of different hen age with different laying position of eggs in the incubator on the hatchability of eggs. This research used Completely Randomized Design (CRD) with factorial pattern 2x2 and five replication. The first factor that was age of hens (1.5 years ; 2.5 years) and the second that was laying position of eggs in incubator (vertical ; horizantal). The result showed that laying position of eggs in the incubator and interaction of hens age with laying position of eggs in the incubator were not significant (P>0.05) on the eggs fertility, hatchability and the weight of day old chicken (DOC). The average of eggs fertility on ninth days was 86,5% and decreased on the fourteenth was 79%. The average of eggs hatchability was 71%. Where as different of hens age was not significant on egg fertility and hatchability (P>0.05) but was significant on egg weight (P